Management of Potential Mental Health and Behavioral Disorders for College Students Using Integrated Applications: Implementation of Human-Centered Design - Rinda Nurul Karimah; Dia Bitari Mei Yuana; Reza Putra Pradana; Prawidya Destarianto; Dhyani Ayu Perwiraningrum (Jurnal Teknologi Informasi dan Terapan, 2026)
Symptoms of mental disorders among college students have risen recently. A comprehensive synthetic review using a socio-ecological model as a guiding framework reveals that college students' mental health is influenced by several dynamic and interconnected factors at the individual, interpersonal, institutional, community, and policy levels, all of which can contribute to stress, anxiety, and depression. Several information and communication technology (ICT) services have been developed to improve healthcare, including the Depression, Anxiety, and Stress Scale 21 (DASS21) instrument. However, these applications do not receive continual monitoring and support from mental health professionals such as psychologists. To address the mental health difficulties of adolescent college students, it is critical that the services established provide appropriate interventions and successfully identify, detect, and address student mental health concerns. As a result, when creating an application interface, a Human-Centered Design (HCD) approach is required, which prioritizes human interaction to provide a more intuitive, precise, and user-friendly user experience. The success of the HappyMind app design was demonstrated by testing it on target users, namely college students, and end users, especially psychologists who served as evaluators. The results demonstrate that the HappyMind application design achieved an average score of 4 or 5, particularly for simplicity of use, text clarity, comfort, and visual appeal.